Energia de superfície para nanossuperfícies de TiO2 na direção (001) - Lazaro, Sergio de; Penteado, Renato Ferras; Tebcherani, Sergio Mazureck; Berger, Danielle [UNESP]; Varela, José Arana [UNESP]; Kubaski, Evaldo Toniolo (Sociedade Brasileira de Química, 2012)
In this work was made an investigation about bulk and surface models (at maximum 20 layers) of the TiO2 material in the (001) direction. TiO2 commercial sample was feature using XDR technique to determine phase and crystallites average size. Bulk and (001) surface models were simulated for TiO2 material using DFT/B3LYP and its results were used for calculating energy surface, electronic levels, superficial atomic displacement and charge maps. Atoms of the first and second layers of the slab model showed electronic densities very well organized in the form of chains or wires.
Surface energy for (001) TiO2 nanosurfaces
Keywords: DFT; TiO2; rutile